Differential Extent of Opportunity Among Executives and Lower Managers - OʼDonovan, Thomas R. (Academy of Management Journal, 1962)
Presents a study which discussed the factors associated with career development and opportunities among executives and lower managers. Methodology and study groups; Limitations of the study; Results and discussion; Summary and implications.